Sharia Life Insurance in Indonesia - Syahlan Sobirin; Milla Maulidina Putri; Dewi Indriyani; Dea Viviyanti (Journal of Islamic Business and Economic Review, 2021)
Sharia Life insurance is an institution that has an important role in Indonesia, because its activities play a role in protecting the risk of unexpected financial life caused aby someone's death. Sharia Life insurance is to minimize the occurrence of an accident that is not desired by someone, because a disaster will come without the person's knowledge. With an insurance company, a person can be borne by the insurance company. Insurance companies as service companies, on the one hand sell services to customers or customers, while on the other hand insurance companies as investors from public savings to productive investments., implementation of the settlement of sharia life insurance claims to its customers and obstacles in the implementation of the settlement of sharia life insurance claims to its customers at sharia life insurance company. The results of this study explain that in the implementation of the insurance agreement the customer is entitled to determine, for the implementation of claim settlement is very easy because the insurance company will help manage the claim in question and immediately get the compensation money, and for the settlement of obstacles will provide solutions to find a bright spot.